Controllable synthesis of dual-MOFs nanostructures for pH-responsive artemisinin delivery, magnetic resonance and optical dual-model imaging-guided chemo/photothermal combinational cancer therapy. (September 2016) - Wang, Dongdong; Zhou, Jiajia; Chen, Ruhui; Shi, Ruohong; Zhao, Gaozheng; Xia, Guoliang; Li, Ren; Liu, Zhenbang; Tian, Jie; Wang, Huijuan; Guo, Zhen; Wang, Haibao; et al.
Abstract: Theranostic nanoagents which integrate diagnostic and therapeutic moieties into a single platform have attracted broad attention in cancer therapy, however the development of more effective and less toxic diagnostic and therapeutic interventions is still of great urgency. Herein, novel core-shell PB@MIL-100(Fe) dual metal-organic-frameworks (d-MOFs) nanoparticles are fabricated and their combined theranostic effects in vitro and in vivo are investigated. The d-MOFs nanoparticles can serve as a T1 -T2 dual-modal magnetic resonance imaging (MRI) contrast and fluorescence optical imaging (FOI) agent due to the existence of inner PB MOFs and outer MIL-100(Fe) MOFs. The artemisinin (a traditional Chinese anticancer medicine) with a high loading content of 848.4 mg/g is released from the d-MOFs upon tumor cellular endocytosis due to the pH-responsive degradation of outer MOFs in low pH lysosomes of tumor cells. Furthermore, the inner PB MOFs can be utilized for photothermal therapy due to its strong absorbance in NIR region. Under the guidance by such dual-modal imaging, in vivo photothermal and chemotherapy is finally carried out, achieving effective tumor ablation in an animal tumor model. Furthermore, histological analysis revealed that the drug delivery system had no obvious effect on the major organs of mice due to the low toxicity of both d-MOFs and artemisinin. The distinctive multimodal imaging capability, excellent synergistic therapy effect through the combined chemo-photothermal therapy together with the low toxicity of both d-MOFs and artemisinin endow the theranostic nanoagent a promising next generation of nanomedicine for efficient and safe cancer therapy. Graphical abstract: A versatile dual-MOFs (PB@MIL-100(Fe)) structure, serving as an effective dual-model therapeutic agents, which combines photothermal-therapy and chemotherapy of ART, was developed for theranostic agent of cancer in vitro and in vivo.